Experiences and benefits of positron emitted tomography-computed tomography (PET-CT) combined with video-assisted thoracoscopic surgery (VATS) in the diagnosis of Stage 1 sarcoidosis - Luh, Shi-ping (Zhejiang University Press, 2007)
Background: The purpose of this study was to describe our experiences and analyze the benefits of video-assisted thoracoscopic surgery (VATS) combined with positron emitted tomography (PET)-computed tomography (CT) in the diagnosis of patients with early (Stage 1) sarcoidosis. Methods: From 1995 to 2006, seven patients (two males, five females), with ages ranging from 26 to 58 years, were impressed with Stage 1 sarcoidosis (mediastinal or hilar lymph nodes involvements without lung involvement) by histological examination of intrathoracic lymph nodes (LNs) and/or lung parenchyma taken from VATS biopsy. Three of them received PET or PET-CT evaluation. VATS was approached from the right and left side in one and six patients, respectively, according to the locations of their lesions. Results: All the VATS biopsied LNs or lung specimens were adequate for establishing diagnosis. Mediastinal LNs were taken from Groups 3, 4 in four, Group 7 in two, and Groups 5, 6 in one of them. Hilar LNs biopsies were performed in four cases. Lung biopsy was performed in all but two cases. All of them were expressed pathologically or radiologically as Stage 1 sarcoidosis. PET-CT revealed high emission signals over these affected LNs. These patients received oral steroid treatment or follow up only. All of them were followed up from 5 months to 11 years with satisfactory results. Conclusion: VATS biopsy is a minimally invasive, safe and effective procedure. It can be used as a diagnostic alternative of transbronchial lung biopsy (TBLB), and can harvest larger and more areas of specimens than mediastinoscopy for staging patients with sarcoidosis. PET-CT can provide us more accurate information about the characteristics and localization of these lesions before biopsy. VATS combined with PET-CT can provide more accurate and earlier diagnosis of patients with unknown intrathoracic lesions, including the sarcoidosis.